Defense spending and economic growth: a look into the former members of the iron curtain - Birdsall, Stephanie (Kansas State University, 2016)
The effects of military expenditures on an economy are characterized by a lack of agreement amongst economists. Classical economists, or free-market thinkers, contend that spending on defense diverts resources from more efficient purposes. On the other hand, Keynesians or those of the Structurialist school, argue that defense spending can improve economic growth through the improvement and construction of important infrastructures. Research prior to the 1990’s was identified through a non-econometric approach which we will denote as the First Generation. Economists would analyze the issue from a theoretical standpoint. This provided the foundation for research from the 1990’s onward, as econometric tools became more sophisticated. In recent years, economists have been able to test the legitimacy of the theories put forth in the first generation. Despite the use of various models, including least-squares regressions, endogenous growth, growth curves, economists still lack a general consensus. Furthermore, many models suggest that there is no relationship between economic growth and military expenditures at all. This paper explores ideas from both a theoretical and econometric point of view, standpoints of which includes a positive, negative, or no relationship, between military expenditures and economic growth. From our analysis, we argue that the best approach involves a country by country analysis as opposed to a generalized view. Each country has its own characteristics that can influence the relationship between defense spending, or any other factors, and economic growth.
Keywords: Economics